Genocides by the oppressed : subaltern genocide in theory and practice - Robins, Nicholas A., 1964-; Jones, Adam, 1963- (Indiana University Press, 2009)
In the last two decades, the field of comparative genocide studies has produced an increasingly rich literature on the targeting of various groups for extermination and other atrocities, throughout history and around the contemporary world. However, the phenomenon of "genocides by the oppressed," that is, retributive genocidal actions carried out by subaltern actors, has received almost no attention. The prominence in such genocides of non-state actors, combined with the perceived moral ambiguities of ret